Creative writings in preparing undergraduate pharmacy theses/ Ibtisam Abdul Wahab and Hannis Fadzillah Mohsin - Abdul Wahab, Ibtisam; Mohsin, Hannis Fadzillah (UiTM Cawangan Johor, 2019)
Creative writing in preparing undergraduate pharmacy theses is necessary when students assimilate their knowledge in retail pharmacy by transcribing their experiences and understandings of the herbal products, after the attachment training. It is firstly anticipated that most herbal consumers are not mindful to the botanical designations of those species. Therefore, the students need to describe natural sources with the local descriptions. In their proposals, the literature would cover the scientific explorations of that native plantarum. Then, the students would be able to relay the information to the public, after extensive readings in Semester Five. Fortunately, some foreign plant samples are not difficult to be investigated, due to their accessibility in the outlets. Nevertheless, the challenges are more concentrated on the modern therapeutic applications of those herbs, as compared to their utility in traditional practices. In Semester Six, the undergraduates' examinations would involve the laborious analysis of the extracts, since the ingredients are the active compounds, biosynthesized in plants. The thesis would include the write-up of their communication with the community, regarding the feedback of the current affairs in nutraceutical and pharmaceutical industries. Finally, the students' creativity could be enhanced, when they are required to refer to various resources, in addition to the scientific journals and chemical databases. This includes referring to the holy text while studying the prophetic herbs and custom medicines. In summary, it is believed that creative writings and appraisals are essential in the teaching and learning process and are significant in the career development of the future pharmacists.